Adverse Events Of Atovaquone-Proguanil Compared With Mefloquine as Malaria Chemoprophylaxis Used By Visitors Of Malaria Endemic Country : A Systematic Review And Meta Analysis - Tammubua, Jerroll Septian; Giri, Made Kurnia Widiastuti; Rahmadewi, Made Ayu Rahayu Agastyane; Tresnadinata, I Made Lingga; Febryanti, Made Devina; Pradnyadewi, Ni Putu Cempaka Pradnyadewi (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Introduction: Chemoprophylaxis plays a crucial role in preventing malaria among travellers to endemic regions. Atovaquone-proguanil and mefloquine are two of the main chemoprophylactic agents recommended by the WHO and CDC to prevent malaria. Both are effective in malaria prophylaxis but are associated with distinct adverse events that can influence their use in travellers. Method: Literature search was conducted in ScienceDirect, and PubMed databases until 2025 without language constraints. Inclusion criteria focused on studies assessed the use of both atovaquone-proguanil and mefloquine as malaria prophylaxis in visitors to malaria-endemic countries. The risk of bias was evaluated using TheNewcastle-Ottawa Scale and Cochrane